(Ignoring) the Prosperity Playbook. Issue 5 (19th October 2016) - Menaldo, Victor
ABSTRACT: Why are some countries poor? It comes down to good governance: secure property rights and policies that reduce transaction costs. In turn, this means the rule of law: limits on executive authority and a government that impartially enforces contracts, and thus abstains from picking winners. It also means a government that solves market failures. Yet the governments of developing countries often do the opposite. The proximate reasons are the endurance of state monopolies, policies that cripple the rural sector, and an over-dependence on natural resources. The deeper reason is rulers' need to raise revenues in short order to survive.